Pengaruh Gaya Kepemimpinan Berorientasi Tugas terhadap Kinerja Karyawan melalui Efisiensi Kerja dan Efektivitas Kerja sebagai Variabel Intervening (Studi Kasus pada PT. Polygroup Manufaktur Indonesia) - Hidayat, Mukhamad Andrean Rahmat; Sumiati, Siti (ARZUSIN, 2026)
This study was motivated by the importance of improving employee performance in manufacturing companies through the application of an appropriate leadership style, particularly in addressing issues related to production target achievement, resource-use efficiency, and employee work effectiveness at PT Polygroup Manufaktur Indonesia. This study aimed to analyze the effect of task-oriented leadership style on employee performance through work efficiency and work effectiveness as intervening variables. This study used a quantitative approach with a survey method. Data were obtained through the distribution of questionnaires to 100 employees of PT Polygroup Manufaktur Indonesia selected using purposive sampling. Data analysis was conducted using the Partial Least Squares-based Structural Equation Modeling (SEM-PLS) method with the assistance of SmartPLS software. The results showed that task-oriented leadership style had a positive and significant effect on work efficiency, work effectiveness, and employee performance. Work efficiency and work effectiveness were also proven to have a positive and significant effect on employee performance. These findings indicate that structured, clear, and target-oriented leadership can improve work efficiency and effectiveness, thereby affecting the improvement of employee performance. Thus, this study affirms that task-oriented leadership style is an important factor in supporting the operational success of manufacturing companies, particularly through strengthening employee work efficiency and effectiveness.